Assessment of Impact of Oil and Gas Exploration and Production on Ecosystem Services and Human Livelihood: A Case Study of West Cape Three Points in the Western Region, Ghana - Ofosu, F. (University of Ghana, 2017)
Ghana's oil and gas industry has been in existence for a decade now. Nonetheless, the quest for local jobs and a boost in national revenue has been a major focus with a lesser consideration for environmental and social ramifications. This study examined impact of oil and gas activities on ecosystem services and human livelihood in coastline communities West of Cape Three Points in the Western Region of Ghana. The study employed descriptive research design and purposive sampling technique. It involved a social survey and laboratory analysis of soil, sea water, borehole, hand-dug well and fish samples. Both test (main) and control samples of sea, borehole and hand –dug well water were analyzed and compared. Also analyzed were fish and soil samples. Key indicators of water quality such as pH, EC, BOD, DO, TDS and Turbidity were determined. Again were pH, Organic Carbon, EC and CEC of soil as well as heavy metals concentrations of Pb, Cd, Cr, Fe and Ni in water and fish samples. Ethos 900 Microwave and Atomic Absorption Spectrometer (AAS) were used for the quantitative determination of parameters. Data was analyzed using analysis of variance (ANOVA) at 0.05 level of significance, Karl Pearson's Product Moment Correlation at P ≤ 0.05 and the Chi - Square to establish relationship between variables. There were significant differences amongst parameters such as EC, BOD and TDS and heavy metals such as Pb, Ni and Fe based on WHO standards. Trend of fish catch was noticed to be decreasing whiles demographic characteristics like gender, educational background were identified to influence perception of oil and gas impact on beach and shoreline recreation. Moreover, educational background, duration of stay and gender were noticed to influence public perception on visit to the beaches and shoreline. University of Ghana http://ugspace.ug.edu.gh
Keywords: Impact of Oil and Gas Exploration; Production on Ecosystem Services; Human Livelihood